Resilience and psychological well-being among career women - Wan Othman, Wan Norhayati; Wan Jaafar, Wan Marzuki; Mohamad Yusop, Yusni; Zainudin, Zaida Nor (Tarbiat Modares University,Danishgah-i Tarbiyat Muddaris, 2024)
Aims Psychological well-being is an important factor affecting career women’s job satisfaction and performance. Resilience predicts psychological well-being, acting as a catalyst for boosting psychological well-being. This systematic literature review explored the relationship between resilience and psychological well-being among career women. Information & Methods Relevant papers were retrieved using Scopus, ScienceDirect, and PubMed. The inclusion criteria included research published between the years 2012 and 2021 to examine whether there is a relationship between resilience and psychological well-being, as well as the predictors of resilience and psychological well-being. Findings There was a favorable relationship between resilience and psychological well-being, with those having higher levels of resilience reporting greater psychological well-being. Resilience is believed to be one of the most essential variables in maintaining positive psychological wellbeing. Additionally, social and family support, work experience, marital status, education level, and self-esteem were found to predict resilience and psychological well-being. Conclusion Age, life experience, work experience, marital status, level of education, and selfefficacy are key predictors of resilience.